To Target or Not to Target: Active vs. Passive Tumor Homing of Filamentous Nanoparticles Based on Potato virus X - Shukla, Sourabh (Cell Mol Bioeng, 2015)
Nanoparticles are promising platforms for the diagnosis and treatment of cancer. Diverse classes and shapes of materials have been investigated to establish design principles that achieve the effective partitioning of medical cargos between tumors and healthy tissues. Molecular targeting strategies combined with specific nanoparticle shapes confer tissue-specificity on the carriers, allowing the cell-specific delivery of cargos. We recently developed a filamentous platform technology in which the plant virus Potato virus X (PVX) was used as a scaffold. These particles are flexible 515 × 13 nm filaments that encourage passive tumor homing. Here we sought to advance the PVX platform by including a molecular targeting strategy based on cyclic RGD peptides, which specifically bind to integrins upregulated on tumor cells, neovasculature, and metastatic sites. Although the RGD-targeted filaments outperformed the PEGylated stealth filaments in vitro, enhanced tumor cell targeting did not translate into improved tumor homing in vivo in mouse tumor models. The RGD-PVX and PEG-PVX filaments showed contrasting biodistribution profiles. Both formulations were cleared by the liver and spleen, but only the stealth filaments accumulated in tumors, whereas the RGD-targeted filaments were sequestered in the lungs. These results provide insight into the design principles for virus-based nanoparticles that promote the delivery of medical cargos to the appropriate cell types.